2018
DOI: 10.1111/odi.12942
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms and influencing factors of xerostomia among Parkinson’s disease patients

Abstract: PD patients suffer from xerostomia, dysphagia, and drooling. Subjective dysphagia is associated with drooling and xerostomia, but drooling prevalence or intensity does not influence xerostomia symptoms. Tremor, dyskinesia, and disease duration, which characterise PD, affect xerostomia. Additionally, food intake, sleep, age, LEDD, and daytime (peaks at 9 a.m. and 9 p.m.) increase xerostomia occurrence. This knowledge may improve dentists' advice to patients and aid development of patient-centred, symptom-reliev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Consistent with this suggestion, a previous study reported that patients with PD produced significantly less saliva and that decreased production of saliva correlated with the dose of levodopa [22]. Barbe et al also reported an association between subjective dysphagia and xerostomia and that LEDD increased the occurrence of xerostomia [23]. However, the direct effect of dopamine on the sympathetic innervations of the salivary glands that cause a decrease in salivation is unknown.…”
Section: Discussionmentioning
confidence: 72%
“…Consistent with this suggestion, a previous study reported that patients with PD produced significantly less saliva and that decreased production of saliva correlated with the dose of levodopa [22]. Barbe et al also reported an association between subjective dysphagia and xerostomia and that LEDD increased the occurrence of xerostomia [23]. However, the direct effect of dopamine on the sympathetic innervations of the salivary glands that cause a decrease in salivation is unknown.…”
Section: Discussionmentioning
confidence: 72%
“…The dominant manifestations of oral symptom in PD presents salivary excretion, swallowing difficulties, dry mouth, tongue diseases [7], periodontitis and tooth decay [8].…”
Section: Oral Symptoms In Pdmentioning
confidence: 99%
“…Furthermore, Parkinson's medication can cause xerostomia and hyposalivation, thereby contributing to impaired oral health. Barbe et al found that 50% of a PD study population reported xerostomia and up to 87% showed hyposalivation; 13 furthermore, PD patients might have a deviation in the circadian controlled salivary flow rates 14 . Thus, it is important that the dentists have insight into the mechanisms behind xerostomia and decreased salivary secretion and contribute to diagnostics and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary drooling is caused by disorders that affect the centres in the brain that initiate, control and regulate the swallowing process, as well as the motor neurons 16 . In PD, drooling is generally secondary and associated with reduced swallowing frequency and efficiency, and impaired orofacial and oropharyngeal muscle function 14–17 . Therefore, drooling in patients with PD can occur even when there are low salivary flow rates.…”
Section: Introductionmentioning
confidence: 99%